JOINT DAMAGE AFTER FROSTBITE (A CASE REPORT) - Sh. F. Erdes; S. O. Krasnenko; M. M. Urumova (Научно-практическая ревматология)
The paper describes a case of a 36-year-old man with finger joint and bone damage that occurred a year and a half after severe frostbite.